ANALISIS STRATEGI PENGEMBANGAN BISNIS MEBEL MUHAJIR DALAM MENGHADAPI PERSAINGAN DI KECAMATAN BAJO KABUPATEN LUWU - Marhawati Najib; Nuralisa Nuralisa; Andi Caezar To Tadampali; Andi Tenri Ampa; Mustari Mustari (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze the business development strategy of the Muhajir furniture industry in Rumaju Village, Bajo District, Luwu Regency. Established in 2016, this company faces tight competition and limited innovation and marketing. Informants in this study include the owner of the Muhajir furniture industry, production employees, and customers. This study uses a qualitative research method with data collection techniques in the form of observation, interviews using questionnaires, and documentation. The data analysis technique used is SWOT with the Competitive Positioning Analysis approach. The results of this study indicate that strengths such as having various adequate production machines so that they can produce quality products and can facilitate production, but some weaknesses include dependence on wood suppliers as raw materials and lack of online infrastructure. The opportunities for this furniture business include market expansion, which can open up opportunities to reach more consumers, thus increasing furniture sales. Threats include competition with other furniture industries serving the same segment in the Luwu and Palopo regions, as well as machine breakdowns that could hamper production. Through SWOT analysis, development strategies such as digital marketing, product diversification, and risk management are formulated to increase competitiveness and sustainable growth.